Personality traits and BMI trends over three years in Japanese university students. - Nozomi Fukuhara-Makiyama; Masaki Hayashida; Masakazu Kobayashi; Ikuko Sagara; Sayaka Ogawa; Mayumi Maeda; Susumu Shirabe (PLoS ONE)
In Europe and America, associations between personality traits and body-mass index (BMI) have been reported. However, in Japan, the association between personality traits and BMI (i.e., thinness and obesity) has not been well studied. In this study, we investigated the relationship between Temperament and Character Inventory (TCI) personality traits and changes in BMI status among Japanese students during their university attendance. We measured the height and weight of 5,340 students in a Japanese university during annual medical checkups and calculated their BMI. The students' personality traits were measured using the short Japanese version of the TCI at university admission. The participants were divided into seven groups based on how BMI changed from the first year to the fourth year at university. In men, compared to the group that maintained normal BMI status (N = 2,189) over time (i.e., the control group), the group that maintained thinness status (N = 226) were lower in Reward Dependence, and the group whose status improved from thinness to normal (N = 117) were higher in Harm Avoidance. In women, compared with the control group (N = 1,510), the group that maintained thinness status (N = 302) was lower in Novelty Seeking, and the group whose status worsened from normal to thinness (N = 127) was higher in Harm Avoidance. Weak associations were found between thinness and TCI personality traits among Japanese university students. Further elaboration of the relationship between obesity or thinness and personality traits may help to provide effective preventive interventions in these areas.